Real time automated video surveillance system with firearm detection capability - Bermudez, Suzanne Rona O. (2004)
Video surveillance is defined as keeping as rea under which and determining if the presence of a person or thing makes the surveyed area 'unsafe'. A particular concern is determining when a person is in possession of a firearm. We present a video surveillance system that uses standard image understanding techniques to detect if a person is carrying a firearm. We have three modules: Image Segmentation, Human Region Selection and Firearm Detection. Image segmentation is concerned with separating the moving foreground region from the background. The system uses color and brightness component separation to distinguish the background from the foreground. The largest blob is then selected and processes for presence of long and thin protrusions. Comparison between subsequent frames that sill show the presence of the suspected firearm triggers the alarm. As the system needs to perform in real-time to be effective, we also employed optimization techniques that work to lessen the system's processing time as well as increase the accuracy of firearm detection. Experimental results show the system can function well even under non-ideal conditions (i.e. presence of shadows, same color background and foreground, and occluded firearm).